Dynamic modeling and experimental study of hybrid compliant mechanism stretching trapezoidal membrane. (1st March 2022) - Zheng, Yu; Yang, Yang; Han, Shaofeng; Ma, Ke
Highlights: A novel hybrid compliant mechanism (HCM) with a force-sensing tip is proposed and the pseudo-rigid-body model (PRBM) of the proposed HCM is given. The stretched membrane is modeled as trapezoidal linear elastic element. A dynamic interaction model which describes the dynamic process of HCM stretching trapezoidal membrane is proposed. The dynamic interaction model is verified by stretching polydimethylsiloxane samples and human anterior lens capsule samples with the proposed HCM. Abstract: Controlling the operation force in membrane peeling is a challenging task in ophthalmic surgery. Hybrid compliant mechanism (HCM) provides a feasible method to address this problem. In this method, operation force is controlled by stretching the clamped trapezoidal membrane. The operation force is related to the dynamic characteristics of the HCM and trapezoidal membrane. This study aims to build a dynamic interaction model that describes the dynamic process of HCM stretching trapezoidal membrane. An HCM with a force-sensing tip is proposed, and the pseudo-rigid-body model of the proposed HCM is given. The trapezoidal membrane is regarded as a variable cross-section linear elastic element. Then, the dynamic model of HCM and trapezoidal membrane are developed using the Lagrange equation. The constraint relationship between HCM and trapezoidal membrane is derived, and the dynamic interaction model is developed. Finally, the dynamic interaction model is verified by stretching six polydimethylsiloxanes (PDMS) samples and two human anterior lens capsule (ALC) samples with the proposed HCM. Experimental results show the average relative errors of the dynamic interaction model are 10.78% (PDMS) and 8.79% (human ALC), respectively. Graphical abstract: Image, graphical abstract